The HarvestPlus REU/A2Z-AED 2007-2008 Uganda 24-Hour Recall Survey - International Food Policy Research Institute; Academy for Educational Development (International Food Policy Research Institute, 2017)
This dataset is composed of two 24-hour recall surveys conducted by HarvestPlus in 2007 as a baseline for its Reaching End Users (REU) project and by AED in 2008 in the context of the A2Z project. The two surveys aimed at estimating food and nutrient intakes of women and children and shared data collection tools including the food composition table.